Kevin P. Spicer, Ed. and Martina Cucchiara, Trans. The Evil that Surrounds Us: The WWII Memoir of Erna Becker-Kohen - Menke, Martin (Studies in Christian-Jewish Relations, 2019)
No abstract is available.